Impact of Customer Journey Mapping on Customer Loyalty: The Moderating Role of Customer Satisfaction - Farhina Hameed; Malik Faiq Anjum; Akash Khateeb (UW Journal of Management Sciences, 2025)
Purpose: This study aims to investigate the relationship between Customer Journey Mapping (CJM) and Customer Loyalty (CL), examining the mediating role of Customer Experience (CX) and the moderating role of Customer Satisfaction (CS). While CJM is widely recognized as a tool for enhancing CX, its direct and indirect effects on customer loyalty remain underexplored. This research addresses this theoretical gap by analyzing how CJM practices influence customer loyalty and how customer satisfaction may strengthen this relationship. The study also contributes to the advancement of customer relationship management (CRM) theories. Design and Methodology: A mixed-method approach was employed, incorporating both qualitative and quantitative data. A structured questionnaire was administered to a sample of 357 customers in the textile sector, selected through stratified random sampling to ensure representative responses. Quantitative data were analyzed using descriptive and inferential statistics, with a 95% confidence level and a 5% margin of error. Qualitative data were gathered through customer feedback to provide deeper insights into customer perceptions of CJM and its implications. The study is grounded in Customer Experience Theory and Relationship Marketing Theory, which form the theoretical foundation for the proposed research model. Findings: The results confirm significant relationships between CJM, CX, CS, and CL. CJM has a direct positive effect on customer loyalty. Additionally, customer experience plays a mediating role, with better journey mapping leading to improved experience and, consequently, greater loyalty. Customer satisfaction further strengthens the link between CX and CL, serving as a key moderator in this dynamic. These findings highlight the interdependent nature of these constructs in fostering long-term customer relationships. Implications: The research makes theoretical contributions through understanding how CJM affects loyalty through CX and CS. Practically, it suggests that organizations build CJM strategies that incorporate CX as well as measure customers’ satisfaction to make loyalty happen. Furthermore, this research advocates for an integrated approach to managing customer relationships in highly competitive environments and combines theory and practice to offer tangible implications for firms looking to improve retention and achieve sustainable growth. In highly competitive markets the long-term relationship with customers is managed through it.